Percentage Body Weight Gain During Tuberculosis Treatment: Can It Be a Useful Tool to Predict the Outcome? - Srikanta Kanungo; Jafar Ali Abedi; Mohammad Athar Ansari; Zulfia Khan (Medsci Publications, 2018)
Introduction: This present study was conducted to find out use- fulness of percentage body weight gain in predicting treatment outcome as well as cut off for successful outcome at different point of time (2 months and 6 months) during treatment. Methods: In this prospective study 302 tuberculosis patient under treatment were followed up for a period of fifteen months in a North Indian district. Outcome of treatment was assessed at the end of 15 months of follow up. Percentage body weight gain at  end of 2nd and 6th month was calculated from the baseline body weight. Data was analyzed using SPSS 20.0. Receiver operating characteristics (ROC) curve was used to find out cut off, sensitivity and specificity for prediction of treatment outcome. All p < 0.05 were considered as statistical significant. Results: 86.8% participants had their treatment outcome success- ful. Percentage of body weight gain at the end of 2nd and 6th month was found to significantly predict the outcome of treatment. (AUC=0.64 and 0.7, p < 0.05). Cut off % body weight gain were ≥2.5 % and ≥ 6.4% at the end of 2 months and 6 months respective- ly to predict successful outcome. Conclusion: Percentage body weight gain was found to be a useful predictor of tuberculosis treatment outcome.